2016
DOI: 10.1038/nmeth.3838
|View full text |Cite|
|
Sign up to set email alerts
|

Automated structure modeling of large protein assemblies using crosslinks as distance restraints

Abstract: Crosslinking mass spectrometry is increasingly used for structural characterization of multisubunit protein complexes. Chemical crosslinking captures conformational heterogeneity, which typically results in conflicting crosslinks that cannot be satisfied in a single model, making detailed modeling a challenging task. Here we introduce an automated modeling method dedicated to large protein assemblies ('XL-MOD' software is available at http://aria.pasteur.fr/supplementary-data/x-links) that (i) uses a form of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 45 publications
1
56
0
Order By: Relevance
“…CXMS-based structural modeling has been explored using various software tools, yet a lot of these studies aimed for a single structure that had the lowest energy and best satisfied the experimental data (11,13,24,25). To fully account for the intramolecular cross-links, we developed the DynaXL method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CXMS-based structural modeling has been explored using various software tools, yet a lot of these studies aimed for a single structure that had the lowest energy and best satisfied the experimental data (11,13,24,25). To fully account for the intramolecular cross-links, we developed the DynaXL method.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been shown that for protein-protein complexes, intermolecular cross-links incompatible with a unique complex structure may arise from some alternative arrangement(s) of the complex (11,20). We thus reason that overlength intramolecular cross-links can be explained by the dynamic movement between different parts of the protein.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…A common scenario is to combine cryo-EM with crosslinking data, which also needs to be tested systematically with ISD. A Bayesian approach to modeling macromolecular assemblies with crosslinking data has been proposed recently by Ferber et al (2016). …”
Section: Discussionmentioning
confidence: 99%
“…The model was successfully validated with independent experimental data on protein–protein interactions. XL-MOD [53] also uses a Bayesian framework to reweight conflicting or ambiguous distance restraints from XL-MS, represented as log-harmonic potentials. An elastic network model based on a low-resolution representation of the subunit structures is used to sample conformational changes upon assembly and the component positions and orientations are sampled by a Monte-Carlo optimization scheme followed by relaxation using molecular dynamics.…”
Section: Approaches To Integrative Modellingmentioning
confidence: 99%